2019
DOI: 10.1016/j.concog.2019.102794
|View full text |Cite
|
Sign up to set email alerts
|

The impact of eye contact on the sense of agency

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 50 publications
3
16
0
Order By: Relevance
“…Participants are less likely to look at conspecifics (Kuhn, Teszka, Tenaw, & Kingstone, 2016;Laidlaw, Foulsham, Kuhn, & Kingstone, 2011), or follow gaze cues (Gallup, Chong, & Couzin, 2012) in real-world interactions where the other can observe them, compared with the same interactions in a screen-mediated laboratory setting, where they know their eye movements cannot be observed. This difference is pertinent to Social Agency as it has been demonstrated that direct eye contact from a face stimulus on screen can enhance Temporal Binding effects (Ulloa, Vastano, George, & Brass, 2019). Eye contact is seen to increase self-referential processing, eliciting increased selfawareness (Baltazar et al, 2014) and therefore implicit agency effects (Conty, George, & Hietanen, 2016).…”
Section: Social Agency and Eye Gazementioning
confidence: 95%
See 1 more Smart Citation
“…Participants are less likely to look at conspecifics (Kuhn, Teszka, Tenaw, & Kingstone, 2016;Laidlaw, Foulsham, Kuhn, & Kingstone, 2011), or follow gaze cues (Gallup, Chong, & Couzin, 2012) in real-world interactions where the other can observe them, compared with the same interactions in a screen-mediated laboratory setting, where they know their eye movements cannot be observed. This difference is pertinent to Social Agency as it has been demonstrated that direct eye contact from a face stimulus on screen can enhance Temporal Binding effects (Ulloa, Vastano, George, & Brass, 2019). Eye contact is seen to increase self-referential processing, eliciting increased selfawareness (Baltazar et al, 2014) and therefore implicit agency effects (Conty, George, & Hietanen, 2016).…”
Section: Social Agency and Eye Gazementioning
confidence: 95%
“…Eye contact is seen to increase self-referential processing, eliciting increased selfawareness (Baltazar et al, 2014) and therefore implicit agency effects (Conty, George, & Hietanen, 2016). As this manipulation was without human agency behind the face stimulus or signalling of the participants gaze (Ulloa et al, 2019), it would be of interest for future investigations to introduce these elements, which may improve ecological validity and enhance agency effects even further.…”
Section: Social Agency and Eye Gazementioning
confidence: 99%
“…Thus, 24 volunteers participated in this study (ten females, mean age 31 years (SD 10.3)). To get a vague sense of a minimum sample size we referred to the aforementioned studies on TB in social contexts (Grynszpan et al, 2019 ; Obhi & Hall, 2011a ; Pfister et al, 2014 ; Sahaï et al, 2019 ; Stephenson et al, 2018 ; Ulloa et al, 2019 ). The paradigms used in these studies cover a broad range of designs and methods.…”
Section: Methodsmentioning
confidence: 99%
“…Recent experimental data could demonstrate TB while leading the gaze of a face-like stimulus during joint attention states (Stephenson et al, 2018 ). Additionally, direct eye contact generally seems to increase TB for gaze movements (Ulloa et al, 2019 ). These data suggest that the presence of a social stimulus is already sufficient to result in decreases in duration judgments and hence in an increased TB.…”
Section: Introductionmentioning
confidence: 99%
“…The sense of agency is of utmost value when it comes to controlling an external device, as it will in uence its technology effect, and thus in uencing people's commitment and performance toward that task (26). Participants in this study identi ed a prominent barrier of the virtual-based pharmacy training being the absence of eye contact, which is of particular relation to the sense of agency (27) while the other ve suggested barriers were less appreciated in terms of majority, though they might be still valid for future discussion including, in descending perception, lack of quiet place, technical support, and time.…”
Section: Discussionmentioning
confidence: 88%